(untitled) (Damascus University Journal for engineering sciences, 2023)
In buildings that contain slabs with dropped beams, many openings in these beams are necessary for the passage of services such as water supply networks, ventilation, electricity, telephone, sewage, computer networks. But these openings will reduce the resistance of these beams in a way that will affect the structural work of the beam, and strengthening with one of the available means will be the only option to restore the resistance. This research includes conducting an analytical study using the finite element method to study a comparison between two methods of strengthen openings in reinforced concrete beams using FRP and steel plates. These considered beams are simple in support of rectangular section with an opening in the body in the cut area without any additional reinforcement, the open is square in shape. Several results have been reached confirming that the use of steel sheets to reinforce the hole contributed to raising the resistance of the beam by about 95% compared to the beam equipped with an unreinforced hole. As for the reinforcement using fiber-reinforced polymers FRP, the difference was about 33%, so we find that strengthening the hole using metal sheets It is the ideal solution to restore the proper structural work of the permissible.